Gerenciamento de resultados e estrutura de propriedade nas companhias de capital aberto no Brasil - Holanda, Allan Pinheiro (2012)
The accounting information that has the quality attribute can be an important tool to reduce agency conflict effectively, to efficiently transmit the economic situation of the firms investors and potential investors, and among the various ways to detect the quality of accounting information, there is earnings management, whose intensification is related to a lower quality of accounting information. The aim of this research is to identify the association between the ownership structure of public companies in Brazil and the propensity of their managers to practice earnings management. To measure the practice of earnings management used the measures developed by Leuz, Nanda and Wysocki (2003) and Zimmerman and Goncharov (2003). And as characteristics of ownership structure characteristics were used a number of characteristics relating to the control of the firm, institutional investors, minority shareholders and the situation of the firm as governance and marketability of its shares. The data for the measurement of variables were obtained in the database Economática ®, in the Reference Forms Annual Information and the Financial Statements are available in institutional portals of the BM&FBovespa and the Securities and Exchange Commission (CVM) for the period 1998 to 2010. The empirical inferences were based on descriptive statistics, tests of means, correlation analysis and multiple regression analysis. Based on the results found in the empirical tests, we can’t reject the hypothesis that the level of earnings management in public companies of Brazil is significantly affected by your ownership structure.